Prevalence and Perpetrators of Domestic Violence against Adolescents in Rivers State. - Okey-Orji, Stella; Asogwa , Emmanuel U. (Archives of Business Research, 2020)
The study investigated prevalence and perpetrators of domestic violence against adolescents in Rivers State. Cross sectional and co-relational designs were used for the study. Three research questions guided the study and four hypotheses were postulated and tested. The population for the study was 93,076 adolescents in Rivers State Senior Secondary Schools. A sample size of one thousand five hundred and twelve (1512) respondents was selected using multistage sampling procedures. The instrument for data collection was validated self-structured/adapted 59-item questionnaire titled domestic violence prevalence and perpetrators questionnaire (DVPPQ). The data generated were subjected to statistical analysis using mean and standard deviation to answer the research questions, while Z-test and ANOVA were used to test the hypotheses at 0.05 alpha levels. The findings of the study revealed that domestic violence against adolescents was prevalent in Rivers State with grand mean of 2.63. Guardians, siblings and parents were the major perpetrators of physical, verbal, economic and emotional abuses, while relatives, friends and neighbors were the perpetrators of sexual abuse against adolescents. The findings also revealed that age, parents’/guardians’ educational and occupational status had no significant influence on the perpetration of domestic against adolescents but gender did. Based on the findings, the study recommended among others that integrated approaches be adopted to curb the menace of domestic violence in the society, particularly in Rivers State.